2023
DOI: 10.1101/2023.01.16.23284593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout: A Predictor of Oral Health Impact Profile Among Nigerian Early Career Doctors

Abstract: Introduction There have been reported association of oral health disorders with burnout, stress, and mental health. Arguably, with these reported associations, and the current prevalence of burnout amongst Nigerian doctors, exploring the role of burnout on oral health amongst Nigerian doctors is timely. This study aims to determine the relationship between burnout and oral health-related quality of life amongst Early Career Doctors (ECDs) in Nigeria, while also identifying the role other possible predictors pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A multistage cluster sampling technique was used, and 31 centers were randomly selected using simple random sampling technique (balloting) from a list of all centres across the 6 geopolitical zones as follows: Northwest (5), Northcentral (7), Northeast (3), Southsouth (5), Southwest (9) and Southeast (2). Five to ten departments were then randomly selected using a simple random sampling technique (balloting) from a list of all the departments in each Centre.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…A multistage cluster sampling technique was used, and 31 centers were randomly selected using simple random sampling technique (balloting) from a list of all centres across the 6 geopolitical zones as follows: Northwest (5), Northcentral (7), Northeast (3), Southsouth (5), Southwest (9) and Southeast (2). Five to ten departments were then randomly selected using a simple random sampling technique (balloting) from a list of all the departments in each Centre.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%
“…A systematic review of burnout among Nigerian doctors reported burnout ranged from 23.6% to 51.7% [7]. Studies carried out among resident doctors in Nigeria reported high level of stress and exhaustion due to excessive working hours, time pressure, having to deal with patients.…”
Section: Introductionmentioning
confidence: 99%